T3 and T4 decrease ROS levels and increase endothelial nitric oxide synthase expression in the myocardium of infarcted rats - de Castro, Alexandre Luz (2015)
Myocardial infarction leads to a reduction in nitric oxide (NO) bioavailability and an increase in reactive oxygen species (ROS) levels. This scenario has been shown to be detrimental to the heart. Recent studies have shown that thyroid hormone (TH) administration presents positive effects after ischaemic injury. Based on this, the aim of this study was to evaluate the effect of TH on NO bioavailability as well as on endothelial nitric oxide synthase (eNOS) expression after myocardial infarction. Male Wistar rats were divided into three groups: Sham-operated (SHAM), infarcted (AMI) and infarcted + TH (AMIT). During 26 days, the AMIT group received T3 and T4 (2 and 8 µg/100 g/day, respectively) by gavage, while SHAM and AMI rats received saline. After this, the rats underwent echocardiographic analysis were sacrificed, and the left ventricle was collected for biochemical and molecular analysis. Statistical analysis: one-way ANOVA with Student–Newman–Keuls post test. AMI rats presented a 38 % increase in ROS levels. TH administration prevented these alterations in AMIT rats. The AMIT group presented an increase in eNOS expression, in NOS activity and in nitrite levels. TH administration also increased PGC-1α expression in the AMIT group. In conclusion, TH effects seem to involve a modulation of eNOS expression and an improvement in NO bioavailability in the infarcted heart.